A Review on Video Game Places: Examples of Metro 2033 and Metro: Last Light: A REVIEW ON VIDEO GAME PLACES: EXAMPLES OF METRO 2033 AND METRO: LAST LIGHT (Journal of Interior Design and Academy, 2022)
In this study, the history of video games with a commercial history of 50 years is explained. Their development in the process from the first video game venue to the present has been explained and some video games that can be described as milestones are included. Afterwards, the importance of the relationship between video games and architecture was tried to be emphasized and spatial studies were made over two video games released in 2010s. At the end of the study, the importance of virtual spaces for architecture is emphasized in today's world, where all concepts are replaced by virtual versions. When the studies in the literature are examined, although fictional relations such as cinema-architecture relationship, theater-architecture relationship, painting-architecture relationship and its relationship with architecture are examined, it is seen that there are generally deficiencies in the literature on the video game-architecture relationship and the spaces where the games are played. It is expected that the study will contribute to this issue.
Keywords: Digital space; interior design; architecture-video game relationship; virtual space